Modern Trends and Prospects for the Development of Russian Healthcare: The Role of Digital Technologies - V.I., Yudin; O.V, Shirokova (KnE Social Sciences, 2021)
Health care as an open system is affected by external fluctuations: the processes of globalization, digitalization and informatization; modernization and virtualization; increasing complexity of problems and volumes of information; increasing share of qualified, creative work; challenges and threats of the future, increasing social tension and devaluation of values. All this leads to a change in the management paradigm, which is based on future management, advanced development, self-education and self-development. Data analysis of VTSIOM secondary sociological studies and author’s analysis of the content of discussions from August 2018- to February 2019 of medical professionals ’online communities were conducted. The study has identified the following current trends: the growth of informatization, virtualization, the emergence of new medical technologies, the formation of the global medical market, the change in the management paradigm of public and non-profit health organizations, the formation of new requirements for managers and staff of medical organizations. Global trends are linked to the growing popularity of digital healthcare. Medical institutions, diagnostic laboratories and insurance companies are gradually getting involved in the digitalization process and creating a single electronic system. This task is included in the National strategy for the development of artificial intelligence in Russia. The study has fixed that the problem of accessibility and quality of medical care in the country remains relevant, which is confirmed by the data of independent sociological studies. The main risks of digital medicine development are data security and insufficient professional competence of medical personnel in the field of information technology. It is important to support the processes the of users number of medical relevant social networks: iVrach.com, imedicina.ru, vrachirf.ru, doctocnarabote.ru, novmed.net, medtusovka.ru, doctornet.ru as well as consolidation of Russian technology companies in developing their own up-to-date software products for digital medicine. Keywords: Digital Healthcare; digital technologies; quality of medical services, telemedicine, Russian healthcare, risks of digitalization Introduction